Latent semantic indexing versus inverted files indexing technique: An evaluation of effectiveness of the retrieval method / Roslan Sadjirin and Nurazzah Abd Rahman - Sadjirin, Roslan; Abd Rahman, Nurazzah (Universiti Teknologi MARA Cawangan Pahang, 2009)
Information retrieval (IR) is part of computer science which studies the techniques of retrieval of information that aim in satisfying users' queries. Therefore. this paper presents the comparison of two different retrieval techniques in information retrieval which are Latent Semantic Indexing (LSI) and Inverted Files indexing technique. A total of 210 of Malay translated hadith documents from hadith Sahih Muslim and Hadith Sahih Bukhari were used to study the comparison of these retrieval techniques. The result of comparison signifies that retrieval method used in LSI performed better compared to the retrieval method used in Inverted Files technique.